Severe acute liver disease in adults: contemporary role of histopathology - Clouston, Andrew D.; Gouw, Annette S H; Tiniakos, Dina; Bedossa, Pierre; Brunt, Elizabeth M; Callea, Francesco; Dienes, Hans-Peter; Goodman, Zachary D; Hubscher, Stefan G; Kakar, Sanjay; Kleiner, David E; Lackner, Carolin; et al. (Histopathology, 2024)
Liver biopsies have consistently contributed to our understanding of the pathogenesis and aetiologies of acute liver disease. As other diagnostic modalities have been developed and refined, the role of biopsy in the management of patients with acute liver failure (ALF), acute-on-chronic liver failure (ACLF) and acute hepatitis, including acute liver injury (ALI), has changed. Liver biopsy remains particularly valuable when first-line diagnostic algorithms fail to determine aetiology. Despite not being identified as a mandatory diagnostic tool in recent clinical guidelines for the management of ALF or ACLF, many centres continue to undertake biopsies given the relative safety of transjugular biopsy in this setting. Several studies have demonstrated that liver biopsy can provide prognostic information, particularly in the context of so-called indeterminate hepatitis, and is extremely useful in excluding conditions such as metastatic tumours that would preclude transplantation. In addition, its widespread use of percutaneous biopsies in cases of less severe acute liver injury, for example in the establishment of a diagnosis of acute presentation of autoimmune hepatitis or confirmation of a probable or definite drug-induced liver injury (DILI), has meant that many centres have seen a shift in the ratio of specimens they are receiving from patients with chronic to acute liver disease. Histopathologists therefore need to be equipped to deal with these challenging specimens. This overview provides an insight into the contemporary role of biopsies (as well as explant and autopsy material) in diagnosing acute liver disease. It outlines up-to-date clinical definitions of liver injury and considers recent recommendations for the diagnosis of AIH and drug-induced, autoimmune-like hepatitis (DI-AIH).
Gesehen am 02.12.2024